SYNTHESIS AND CHARACTERIZATION OF SOME COMPLEXES OF CR(III), CO(II), NI(II), AND CU(II)WITH (1-BENZOYL-3-METHYL-1HPYRAZOL- 5(4H)-ONE SYNTHESIS AND CHARACTERIZATION OF SOME COMPLEXES OF CR(III), CO(II), NI(II), AND CU(II)WITH (1-BENZOYL-3-METHYL-1HPYRAZOL- - Al-Sabti, Matheel D; Al-Amiery, Ahmed A H; Al-Majedy, Yasmien K K; Hameed, Anaheed H (Al-Nahrain Journal of Science, 2018)
Cr(III), Co(II), Ni(II), and Cu(II) complexes of (1-benzoyl-3-methyl-1H-pyrazol-5(4H)-one have been synthesized and characterized by elemental analysis, FT-IR, UV/ visible spectra, magnetic susceptibility and molar conductivity. All complexes are expected to have an octahedral structure.